Study guides

☆☆

Q: How would i write 18 minus x?

Write your answer...

Submit

Still have questions?

Related questions

18-(2/x)

(x + 2)(x - 9)

7-x

4 - (x + 6)

(-6) x (-3) = 18 (-10) x (-9) = 90 18 - 90 = -72

X - 7 = 11 X = 11+7 therefore X = 18 18 minus 7 equals 11.

18/x

x^2+3x-18 (x+6) (x-3) = 0 x=-6 x=3 a= 1 r= -6 s=3

You need to be careful in how you write such questions as it is important to know if you mean: x - 12/2 = 18 or (x-12)/2 = 18 If x - 12/2 = 18 then x = 18 + 12/2 x = 18 + 6 x = 24 If (x-12)/2 = 18 then x - 12 = 18 * 2 x - 12 = 36 x = 36 + 12 x = 48

(x2 + 7x - 18) = (x + 9)(x - 2)

5x2 - 27x - 18 = (5x + 3)(x - 6)

That factors to (x - 3)(x + 6)

-6 x -3 = 18 + (-6) = 12

A factor is like this. Original :x^2 + 7x - 18 (( x squared plus six x minus 18) Factored: (x+9)(x-2) ((x plus nine times x minus two))

(x - 3)(x - 18)

3(x + 2) = x - 18 3x + 6 = x - 18 3x - x = -18 - 6 2x = -24 x = -12

(18 x 9) - (19 x 8) = 10

(x - 3)(x^2 + 6)

279-125=x 154=x

cheater == 2[x-3]+3[x-2]=18 2x-6+3x-6=18 5x-12=18 5x=30 x=30/5=6

X2 + 3X - 18 Ask yourself, what two factors of - 18 add to 3? (X + 6)(X - 3) -----------------

Do you mean: 5x + 9 - 7x + 6 = x - 18 If so, you can solve this question at this manner: -2x + 15 = x - 18 3x = -3 x = -1

3(x+2) = x -18 3x+6 = x -18 3x -x = -18 -6 2x = -24 x = -12

2 x 3 x 3 = 18

As an algebraic expression it is simply: 18-x